Bentall Operation with Valved Homograft Conduit - Choudhary, Shiv K. (2000)
Lesions of the ascending aorta associated with aortic valve disease are usually treated by implanting a prosthetic valved conduit (Bentall procedure). In this report, we present our experience in which a valved homograft conduit was used for the procedure. Six patients underwent a Bentall procedure with the use of a cryopreserved valved homograft conduit. Two of the patients had annuloaortic ectasia, 2 had Marfan syndrome, and 1 had an atherosclerotic aneurysm of the aorta. One patient had severe aortic stenosis due to a bicuspid aortic valve, along with an aneurysm and localized dissection of the ascending aorta. In all of the patients, the aortic annulus was substantially dilated, with accompanying moderate-to-severe aortic regurgitation. A standard procedure was performed with moderate hypothermia, cardiopulmonary bypass, and aortic and bicaval cannulation. The ascending aorta and the aortic valve were replaced with a cryopreserved valved homograft conduit (aortic in 5 patients and pulmonary in 1). The native coronary ostia were anastomosed directly to the homograft. Echocardiography, which was performed intraoperatively, before discharge from the hospital, and at follow-up visits (1 to 36 months), revealed good valve function without dilatation of the homograft conduits. There was 1 late death due to Aspergillus fumigatus endocarditis, 6 months postoperatively. In 1 patient, magnetic resonance imaging performed at 24 months revealed normal caliber of the homograft conduit. We conclude that the Bentall procedure can be performed, safely and with excellent results, using cryopreserved homograft conduits.